Increasing promotion of mangrove ecotourism during the Covid-19 pandemic through online media training - Machya Kartika Tsani; Rommy Qurniati; Heryandi Heryandi; Duryat Duryat (Community Empowerment, 2022)
Mangrove ecotourism in Margasari Village is a new tourism that is experiencing problems in promotion due to pandemic conditions and the promotion system is still conventional. The solution proposed by the University of Lampung community empowerment team is to promote through online media such as websites, Instagram, and Facebook. The purpose of this activity is to increase the promotion of mangrove ecotourism in Margasari Village through training in the creation and management of online media. The method of this activity is counseling and training on ecotourism promotion using online media. Some of the outcomes of this activity included the manager's understanding of the importance of promotion, as well as the benefits and opportunities of using online media to promote ecotourism. Websites, Instagram, and Facebook have been created and used for promotional media for Mangrove Ecotourism in Margasari Village.